The Novel LncRNA WASH5P Inhibits Colorectal Cancer Carcinogenesis via Targeting AKT Signaling Pathway - Wei, Hongyun; Mao, Tao; Zhang, Qian; Ren, Keyu; Qi, Xingsi; Zhang, Yunmei; Cao, Bin; Jin, Yanchun; Tian, Zibin; Ren, Linlin (Frontiers in Oncology, 2022)
Emerging evidence has shown that long non-coding RNAs (lncRNAs) play an important role in colorectal cancer (CRC) carcinogenesis, so more specific mechanisms of key lncRNAs in CRC initiation and development are needed. Here, we evaluated the expression profiles of lncRNAs in CRC tissues and identified a novel lncRNA generated from the pseudogene Wiskott-Aldrich syndrome protein (WASP) family homolog 5, termed lncRNA WASH5P. However, the role and potential molecular mechanism of this novel lncRNA in diseases, including CRC carcinogenesis, is unknown. Our present study found that WASH5P was significantly downregulated in CRC cell lines and tissues compared with normal controls. The ectopic expression of WASH5P in CRC cells could significantly inhibit CRC cell proliferation, invasion, and migration. In addition, WASH5P could increase the expression of E-cadherin and decrease Vimentin expression. WASH5P-overexpressing CRC cells developed tumors more slowly in different mouse models. Meanwhile, the overexpression of WASH5P could significantly inhibit AKT activation via suppressing AKT phosphorylation. The treatment of PI3K/AKT (phosphatidlinositol 3-kinase /protein kinase B) signaling agonist 740Y-P rescued WASH5P-reduced AKT phosphorylation and abolished the inhibitory effects of WASH5P on cell viability, migration, and invasion. Moreover, 740Y-P restored the WASH5P-induced downregulation of p-AKT and vimentin and the upregulation of E-cadherin via Western blot. In summary, our findings suggested that the novel lncRNA WASH5P might be a potential candidate biomarker and therapeutic target that could inhibit CRC by repressing the AKT signaling pathway.